The anatomy of a trade collapse: the UK, 1929-33 - O'Rourke, K; de Bromhead, A; Fernihough, A; Lampe, M (University of Oxford, 2018)
A recent literature explores the nature and causes of the collapse in international trade during 2008 and 2009. The decline was particularly great for automobiles and industrial supplies; it occurred largely along the intensive margin; quantities fell by more than prices; and prices fell less for differentiated products. Do these stylised facts apply to trade collapses more generally? This paper uses detailed, commodity specific information on UK imports between 1929 and 1933, to see to what extent the trade collapses of the Great Depression and Great Recession resembled each other. It also compares the free trading trade collapse of 1929-31 with the protectionist collapse of 1931-3, to see to what extent protection, and gradual recovery from the Great Depression, mattered for UK trade patterns.